Ütközet a krumpliföldön . Battle on the potato field - írta: Gergely Miklós és Kovács György. (Magyar Diafilmgyártó Vállalat, 1955)
A tale about farmer Jani Szabó, whose potato plantation was infected by Colorado bugs. He asks help from the Council and spraying trucks are sent from the Plant Protection Station and kill the bugs. Jani now watches his fields carefully and introduces preventive steps to fight the bugs. Mesefilm Szabó Jani burgonyatermesztőről, akinek a földjén megjelentek a kártevő krumplibogarak. Kérésére a Tanács a segítségére siet, és a növényvédő állomásról permetező kocsik jönnek és kiirtják a bogarakat. Jani ezentúl folyamatosan figyeli az ültetvényt, és megelőző intézkedésekkel is harcol a krumplibogarak ellen.